An Analysis of the Effects of Capital Expenditure, Institutional Ownership, and Company Growth on Carbon Emission Disclosure - Fitria Inka Virtagani (Yayasan Ilomata, 2026)
This study examines the determinants of carbon emission disclosure in energy subsector companies listed on the Indonesia Stock Exchange over the period 2022 to 2024, considering the increasing urgency of corporate transparency in addressing climate change and Indonesia’s commitment to reducing greenhouse gas emissions by 43 percent by 2030. The main issue lies in the varying level of corporate compliance in emission reporting, which remains largely voluntary. To address gaps in prior literature, this study provides explicit novelty by focusing specifically on the high-emission energy subsector using recent data and employing a rigorous 18-item Carbon Disclosure Project (CDP) measurement framework. Employing a quantitative approach, panel data derived from 125 firm-year observations were analyzed using multiple linear regression. The findings indicate that only capital expenditure has a positive and statistically significant effect on carbon emission disclosure, while institutional ownership, growth opportunity, and sales growth do not show a significant influence. These results suggest that tangible financial investments are positively associated with environmental transparency, whereas external governance and growth metrics do not exhibit a similar relationship in this context. Ultimately, the findings imply a structural limitation in voluntary disclosure practices, highlighting the potential need for stronger regulatory intervention to ensure that transparency is aligned with broader environmental accountability rather than depending solely on internal resource capacity.